Resettlement in the twenty-first century - Anthony Oliver-Smith; Alex de Sherbinin (Forced Migration Review, 2014)
Deficiencies in planning, preparation and implementation of involuntary resettlement and relocation projects have produced far more failures than successes. Indeed, it is questionable whether resettlement as currently practised could be categorised as a form of protection.